A Bundle of Letters - James, Henry, 1843-1916 (Salt Lake City, UT : Project Gutenberg, 2000)
"A Bundle of Letters" by Henry James is a comic short story published in 1879. Set in a Paris boarding house, the tale unfolds entirely through letters written by international residents to friends and family back home. Each correspondent reveals their personality while commenting on their fellow boarders$1 (Boften with sharp disdain. An earnest American traveler, a snobbish English pair, a pretentious aesthete, an amorous Frenchman, and an aggressively nationalistic German professor all unwittingly expose their own prejudices and pretensions, while remaining oblivious to how others perceive them. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/A_Bundle_of_Letters
Release date is 2000-12-01
Transcribed from the 1887 Macmillan and Co. edition by David Price. Proofing by Andy McLauchan and David Stapleton
Keywords: Epistolary fiction; Paris (France) -- Fiction; Imaginary letters; Boardinghouses -- Fiction